Group intervention for emotion regulation training based on cognitive behavioral therapy (CBT) to reduce stress levels in early adolescents - Adelia Shafira Haramain; Lia Mawarsari Boediman (Jurnal Psikologi Tabularasa, 2024)
ABSTRACTEntering the early adolescent development phase brings many challenges for individuals, which can trigger prolonged stress. Adolescents need to overcome this stress to minimize further impacts, such as social relationship problems, academic difficulties, and psychological issues. This study aims to evaluate the effectiveness Cognitive Behavioral Therapy (CBT)-based emotional regulation training in reducing stress levels in early adolescents. This study used quasi-experimental research type with one-group pretest-posttest design. The participants were six early adolescents (12-14 years old) who exhibited severe levels of stress and emotional dysregulation. Changes in stress levels and emotional dysregulation were measured using the Difficulties in Emotion Regulation Scale-Short Form (DERS-SF) and the Depression Anxiety Stress Scale-21 (DASS-21) before, immediately after, and one month post-intervention. Friedman test results showed significant decrease in the level of emotional dysregulation (p=.04; p<.05) and stress levels (p=.03; p<.05) from pretest, posttest, and follow up. These findings suggest that CBT-based emotion regulation training is effective in improving emotion regulation skills and reducing stress levels in early adolescents.ABSTRACTMemasuki fase perkembangan remaja awal membawa banyak tantangan bagi individu yang dapat memicu stres berkepanjangan. Remaja perlu mengatasi stres yang muncul untuk meminimalisir dampak lebih lanjut seperti masalah hubungan sosial, masalah akademik, hingga masalah psikologis. Penelitian ini bertujuan untuk menguji efektivitas pelatihan regulasi emosi berbasis Cognitive Behavioral Therapy (CBT) untuk membantu menurunkan tingkat stres pada remaja awal. Penelitian ini menggunakan jenis penelitian kuasi eksperimen dengan desain one group pretest-posttest. Partisipan penelitian merupakan enam orang remaja awal (12-14 tahun) yang menunjukkan tingkat stres dan disregulasi emosi yang tergolong berat. Perubahan tingkat stres dan disregulasi emosi diukur melalui skor yang diperoleh sebelum, setelah, dan 1 bulan setelah intervensi berdasarkan alat ukur Difficulties in Emotion Regulation Scale-Short Form (DERS-SF) dan Depression Anxiety Stress Scale-21 (DASS-21 Hasil uji Friedman menunjukkan bahwa adanya penurunan yang signifikan pada tingkat disregulasi emosi (p=.04; p<.05)) dan tingkat stres (p=.03; p<.05) dari pretest, posttest, dan follow up. Temuan ini mengindikasikan bahwa pelatihan regulasi emosi berbasis CBT efektif meningkatkan kemampuan regulasi emosi dan menurunkan tingkat stres pada remaja awal.